Tripod-shaped penta (p-phenylene)s for the functionalization of silicon surfaces - Sánchez-Molina, María; Contreras-Cáceres, Rafael; Díaz-Morilla, Amelia; Valpuesta-Fernández, María; López-Romero, Juan Manuel (My University, 2016)
In order to obtain nanostructured thin films to be used in biosensor devices, several chemical functionalization methods have been developed, such as Click chemistry or Suzuki carbon-carbon coupling reactions on surfaces.1 With the aim to control the orientation and spacing between grafted functional groups on a surface, tripodal oligo (p-phenylene)s have become the ideal anisotropic adsorbates due to their shape-persistent and self-standing characteristics.2 Here we report the synthesis and characterization of several tripod-shaped oligo(p-phenylene)s molecules with legs composed of five phenylene units, compounds 1, 2 and 3. In these structures, each leg is end-capped with an NH-Boc, NH2 and N3 group, respectively. The functional arm contains an acetylene group. The presented synthesis has as key step the Pd-catalyzed Suzuki cross-coupling reaction. In particular, a iodine derivative from the silicon core molecule reacts with the appropriate tetra(p-phenylene) boron derivative, thus generating the final tripod-shaped structure. The azide end-capped leg in 3 is specifically designed for its covalent incorporation on alkynyl terminated silicon surfaces by an easy and reproducible way. As a preliminary study, we present the alkynyl-functionalized silicon wafers nanostructuration with tripod 3 through the cooper catalyzed alkyne-azide cycloaddition (CuAAC) click reaction.
Keywords: Nanoestructuras; Tripod-shaped; Nanostructured; Cycloaddition; Silicon